Educational Leadership and Group Decision Making - Miskat, Miskat (International Conferences SDGs 2030 Challenges and Solutions, 2030)
In an organization that consists of variety of human resources with a different expertisebackground, it can create a dynamic atmosphere. It certainly can be an advantage.However, if the leader cannot managed properly, the diversity can be a conflict, especiallyin group decision-making context. Every individual has his own preferences based ontheir knowledge. Some of them can provide shared information, but there are who haveunshared information that held by just one member. Such conditions led the decisionmaking process was not optimal. These problems need the leader’s attention. Thisresearch was an analytical study to analyze the factors that most affect to the quality ofthe group's decision. Finally, this study shows that factors such as leadership style,knowledge of leader and leadership experience have a considerable influence on thequality of group decisions.